Effects of the interaction between PTSD and ADHD symptoms on the level of reporting psychotic-like experiences: findings from a non-clinical population - Gelner, Hanna; Karska, Julia; Gawęda, Łukasz; Samochowiec, Jerzy; Misiak, Błażej (Frontiers in Psychiatry, 2023)
Objective: Psychotic-like experiences (PLEs) are increasingly being recognized as subclinical phenomena that might predict the development of various mental disorders that are not limited to the psychosis spectrum. Accumulating evidence suggests that attention-deficit/hyperactivity disorder (ADHD) and post-traumatic stress disorder (PTSD) are highly comorbid mental disorders. However, their interactive effect on the occurrence of PLEs has not been investigated so far. Therefore, in the present study we aimed to investigate the effect of interaction between ADHD and PTSD symptoms on the level of psychotic-like experiences (PLEs) in the non-clinical sample.The study included 3000 individuals aged 18 -35 years with a negative history of psychiatric treatment. The symptoms of ADHD and PTSD were assessed using self-reports.Results: There was a significant association of the interaction between ADHD and PTSD with the level of reporting PLEs. This association remained significant after adjustment for age, gender, the level of education, the current vocational situation, lifetime history of problematic substance use, and depressive symptoms. Post-hoc tests demonstrated significantly higher levels of reporting PLEs in participants with positive screening for both ADHD and PTSD compared to other subgroups of participants. Also, individuals with positive screening for one vulnerability (either ADHD or PTSD) reported significantly higher levels of reporting PLEs compared to those with a negative screening for ADHD and PTSD. In turn, no significant differences between individuals reporting one vulnerability, i.e., between those with positive screening for ADHD and those with positive screening for PTSD, were observed.Findings from the present study imply that both PTSD and ADHD symptoms the interaction effect on the level of reporting PLEs that might be of importance for early intervention strategies. However, observed associations require replication in clinical samples.